From literacy to impact: a relationship study on EFL students’ literacy to vocabulary mastery, speaking comprehension, and intercultural awareness - Ratnawati Ratnawati; Aan Suryana; Nadira Maulidia Rahmi; Anju Najwatillah (Interdisciplinary International Journal of Conservation and Culture, 2025)
Literacy has increasingly been recognized as a fundamental component of English as a Foreign Language (EFL) learning; however, limited research has examined its simultaneous relationship with multiple language competencies, particularly vocabulary mastery, speaking comprehension, and intercultural awareness. Addressing this gap, the present study aims to investigate the extent to which EFL students’ literacy is associated with these three essential competencies and to identify learners’ needs related to literacy development. This study employed a quantitative correlational design complemented by needs analysis. Data were collected from 107 primary students through a set of instruments, including a literacy test, a vocabulary assessment, a speaking comprehension test, and an intercultural awareness questionnaire, as well as a needs analysis survey. The data were analyzed using Spearman rho correlation to determine the strength of relationships among variables. The findings revealed significant positive correlations between literacy and all three competencies. The strongest relationship was found between literacy and vocabulary mastery, followed by moderate correlations with speaking comprehension and intercultural awareness. These results indicate that students with higher literacy levels tend to demonstrate better lexical knowledge, improved ability to comprehend spoken language, and greater awareness of cultural diversity. In conclusion, literacy functions as a foundational competence that supports broader language development and intercultural communication. The study highlights the importance of integrating literacy-based and multimodal instructional practices in EFL classrooms to enhance students’ communicative competence and global awareness.